Right upper lobe pulmonary sequestration masquerading clinically and radiologically as malignancy: a case report. Issue 1 (31st January 2023) - Gupta, Ankit; Chetty, Gavin; Hopkinson, David; Rao, Jagan; Chetty, Govind
Abstract: Bronchopulmonary sequestration is a rare disease in which a non-functional region of pulmonary tissue receives an aberrant vascular supply and lacks normal communication with the tracheobronchial tree. We present the case of a 30-year-old female with a primary complaint of unexplained weight loss and no other additional signs or symptoms. In view of this, computed tomography imaging was ordered, showing a 33HU mass in the right upper lobe. A specialist radiologist reviewed the images and concluded that the most likely differentials were mediastinal lymphoma or thymic malignancy. Video-assisted thoracoscopic surgery was performed, when it was seen that no malignancy was present, but rather a bronchopulmonary sequestration. Histology confirmed the diagnosis; the patient fared well post-operatively. Bronchopulmonary sequestration is a rare pathology, with most cases occurring in the lower lung lobes. This case is highly atypical, due to the lack of clinical features and the lesion radiologically mimicking the appearance of malignancy.